Opportunities for marker-assisted selection (MAS) to improve the feed quality of crop residues in pearl millet and sorghum - Hash, C.T.; Bhasker Raj, A.G.; Lindup, S.; Sharma, A.; Beniwal, C.R.; Folkertsma, R.T.; Mahalakshmi, V.; Zerbini, E.; Blümmel, Michael (Elsevier, 2003)
Cereal crop residues (straw, chaff, etc.) are important components of maintenance rations for ruminant livestock in many parts of the world. They are especially important in small-holder crop-livestock production systems in the sub-humid, semi-arid, and arid tropics and subtropics where most of the world’s poorest livestock producers and consumers are found. Taking as examples tropically adapted cereals in the crop improvement mandate of the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), namely pearl millet [Pennisetum glaucum (L.) R. Br.] and sorghum [Sorghum bicolor (L.) Moench], this paper explores opportunities for using marker-assisted crop breeding methods to improve the quality and quantity of cereal crop residues for use as ruminant livestock feedstuffs. In the case of pearl millet, ICRISAT has been heavily involved with several UK-based collaborating research institutes, in development and initial application of the molecular genetic tools for marker-assisted breeding. We have obtained some useful experience in quantitative trait loci (QTL) mapping and marker-assisted selection (MAS) for stover yield, foliar disease resistance, and in vitro estimates of the nutritive value of various stover fractions for ruminants. In sorghum, ICRISAT has focused on initiating a large-scale high-throughput marker-assisted backcrossing program for the stay-green component of terminal drought tolerance—a trait that is likely to be associated not only with more stable grain and stover yield, but which is also expected to contribute to maintenance of ruminant nutritional value of stover produced under drought stress conditions. Conventional and marker-assisted breeding for foliar disease resistance is recommended for dual-purpose cereal improvement, or indeed for improvement of the nutritional value of residues for any crop in which these are used as feedstuffs for ruminant livestock. Practical problems faced and proposed ways of dealing with these are discussed.